If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-96=8(-3p-3)
We move all terms to the left:
-96-(8(-3p-3))=0
We calculate terms in parentheses: -(8(-3p-3)), so:We get rid of parentheses
8(-3p-3)
We multiply parentheses
-24p-24
Back to the equation:
-(-24p-24)
24p+24-96=0
We add all the numbers together, and all the variables
24p-72=0
We move all terms containing p to the left, all other terms to the right
24p=72
p=72/24
p=3
| 2x=3=11 | | -5x+÷=53 | | 3x+18=2x+28 | | 5^(7x-4)=25 | | 6n-(-3)=21 | | -132=-6(1+7r) | | -4x-4x+7x=-10+46 | | 5^7x-4=25 | | 4x-5(3x+14)=-4 | | 5n-(-2)=6 | | 3.6m−2.7=−1.8m | | Y=3÷8y-4 | | 6f+30=-30 | | x+1/5=2 | | 4x+4/2=10 | | 145=-5x-7(1+2x) | | 3n-(-4)=6 | | -5n+5(5n+7)=135 | | m/8+2=9 | | -5x+2(x-11)=-37 | | 4x+12x+49x=-8+8 | | (x-5)/(x+5)=25 | | 1/2x-4=1/5x+2 | | x-1/10=7/20 | | 3w+4=10 | | v-9+2(3v+9)=-7(v+1) | | 6m+2=7 | | 4y+8=2y+6 | | Y=-1÷2y+3 | | -5x=-40-15 | | 5x+1/7-6x-4/10=x/4 | | X+6x-6+4x-12=30 |